التطبيقات الحديثة لعقود المضاربة في المصارف الإسلامية بين التقيد والاطلاق (ماليزيا نموذجا للفترة 2015-2019) - جدايني, ميمي (جامعة الوادي - University of Eloued, 2021)
The study presents and analyses modern applications of Al Mudarabah contracts by the Sharia standards of financial banking institutions by mobilizing resources through Restricted accounts (RA) and Unrestricted accounts (UA), and on the other hand, employing funds through joint Mudarabah, and also analyzing banking risks related to them. The study reached through an analysis of the reality of the contracts in the Malaysian Islamic banking system during the period 2015 -2019 that Al Mudarabah contracts are to attract depositors’ funds by more than 95% of the total funds, while the use of Al Mudarabah is very low due to the inclusion of these contracts on all banking risks in addition to its risks, as well as those risks affecting depositors, banks and investors, and The difficulty of adapting it without compromising its sharia nature
Modern mudarabah contracts in Islamic Banks , restricted or unrestricted Malaysia as a model for the period 2015-2019
مقال
Keywords: المضاربة - حسابات الاستثمار المقيدة - حسابات الاستثمار المطلقة - المصارف الاسلامية - المضارب